Nursing interventions and assessment tool for neonatal abstinence syndrome (NAS): a case report - Lorenzo Righi; Alessia Di Gloria; Nicole Brussolo; Fulvia Marini; Stefano Trapassi (Hygeia Press di Corridori Marinella, 2023)
A newborn female was admitted to the Neonatal Intensive Care Unit 2 days after birth with neonatal abstinence syndrome (NAS). The patient displayed withdrawal symptoms from substance misuse, which was passively absorbed in utero via the placenta. This clinical scenario analysis aims to investigate which nursing interventions are dedicated to restoring normal vital functions in NAS patients and which assessment tool is most commonly used to monitor withdrawal symptoms. NAS is a medical condition that affects newborns of drug-abusing mothers. The clinical presentation can involve different organ systems: the central nervous system (CNS), autonomic nervous system (ANS), gastrointestinal (GI) system, and respiratory system. Possible symptoms include excessive or high-pitched crying, agitation, fever, tremors, sleep disturbance, vomiting, weight loss, seizures, sweating, yawning, sneezing, tight muscle tone, tachypnoea, poor feeding, and uncoordinated suction. A NAS diagnosis can be confirmed by verifying the presence of drugs using biological tests and assessment tools to classify and manage the condition. Several biological tests are available to confirm exposure to a misused substance: urine testing, meconium testing, cord blood testing, and baby hair testing. The most commonly used assessment tool is the Finnegan Score. Treatment for an infant with NAS involves both non-pharmacological and pharmacological interventions and a multidisciplinary team. This team works with the parents, particularly the mother, who must be part of the newborn's healing process.